Memorandum of understanding between Universiti Teknologi MARA Johnson & Johnson Sdn Bhd / Fakulti Sains Kesihatan - Universiti Teknologi MARA, Fakulti Sains Kesihatan (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.